Respon dan Sikap Perawat IGD dalam Menangani Klien dengan Percobaan Bunuh Diri dan Self-Harm: Literatur Review - Eva Fatmah; Shanti Wardaningsih (Faletehan Health Journal, 2020)
Suicide is the third leading cause of death worldwide. Most of the suicide attempters were taken to the emergency room (ER) of general hospitals for treatment. The response and attitudes of emergency nurses have an important role in determining the success of treatment in patients with suicide attempts and self-harm. The purpose of this study is to determine the response and attitudes of emergency nurses in general hospitals in treating patients with attempted suicide and self-harm. Searching for articles was done through Pubmed, ProQuest, Ebsco and Scopus databases with the keywords "emergency department nursing", "suicide", "nurses' attitudes". Then an analysis was carried out according to the inclusion and exclusion criteria to determine the appropriateness of the articles. From the results of the study of 8 articles, it was found that the ER nurses showed a negative response and attitudes towards patients with suicide attempts and self-harm. They needed standardized guidelines or protocols from hospitals as a reference in treating patients with psychiatric emergencies. Other needs of ER nurses are education and training in emergency psychiatric management. Most of the nurses showed poor attitudes and response towards patients with attempted suicide and self-harm. It occurred as a result of the lack of emergency psychiatric education and training and lack of hospital protocols.